2019
DOI: 10.1002/chem.201804995
|View full text |Cite
|
Sign up to set email alerts
|

Ce(IO3)2F2⋅H2O: The First Rare‐Earth‐Metal Iodate Fluoride with Large Second Harmonic Generation Response

Abstract: What is the most significant result of this study?In recent years, extensive research and continuous development have been presented on second-order nonlinear optical (NLO) crystal materials due to their potential applications in telecommunications, optical information processing, and optical data storage. In this study,t he first rare-earth iodate fluoride, Ce(IO 3 ) 2 F 2 ·H 2 O, has been synthesized, The results show that Ce(IO 3 ) 2 F 2 ·H 2 Oi sa ni odate fluoride with an ew structure and has potential ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 70 publications
1
38
0
Order By: Relevance
“…Dipole moment calculations were performed to estimate the SHG contribution of SHG‐active units. The local dipole moment of an [IO 3 ] − group was calculated to be 13.09–15.06 D, which was in good agreement with those of reported iodates . The x and z components of the total polarizations from all four [IO 3 ] − groups within one unit cell counteracted each other completely, while the components added up to a net dipole moment of 32.55 D. It has been reported that the SHG contribution of [IO 3 ] − in Bi(IO 3 )F 2 (11.5 KDP) was 77.1 %, corresponding to 8.86 KDP.…”
Section: Figuresupporting
confidence: 84%
See 1 more Smart Citation
“…Dipole moment calculations were performed to estimate the SHG contribution of SHG‐active units. The local dipole moment of an [IO 3 ] − group was calculated to be 13.09–15.06 D, which was in good agreement with those of reported iodates . The x and z components of the total polarizations from all four [IO 3 ] − groups within one unit cell counteracted each other completely, while the components added up to a net dipole moment of 32.55 D. It has been reported that the SHG contribution of [IO 3 ] − in Bi(IO 3 )F 2 (11.5 KDP) was 77.1 %, corresponding to 8.86 KDP.…”
Section: Figuresupporting
confidence: 84%
“…As a result, a series of excellent iodate SHG crystals have been reported, including AMoO 3 (IO 3 ) (A=Rb, Cs), BaNbO(IO 3 ) 5 , NaI 3 O 8 , A 2 Ti(IO 3 ) 6 (A=Li, Na), (NH 4 )[MoO 3 (IO 3 )], ReI 5 O 14 (Re=Y and Gd), BiO(IO 3 ), and Bi 2 (IO 4 )(IO 3 ) 3 . Recently, fluorine‐containing iodates, such as Bi(IO 3 )F 2 , Bi 3 OF 3 (IO 3 ) 4 , ABi 2 (IO 3 ) 2 F 5 (A=K, Rb, Cs), α‐ and β‐Ba[VFO 2 (IO 3 ) 2 ], α‐ and β‐Ba 2 [VO 2 F 2 (IO 3 ) 2 ]IO 3 , α‐ and β‐Ba 2 [GaF 4 (IO 3 ) 2 ](IO 3 ), RbIO 2 F 2 , CsIO 2 F 2 , and Ce(IO 3 ) 2 F 2 ⋅H 2 O, have been demonstrated to be new types of promising NLO iodate crystals. The introduction of fluoride into iodates can not only enrich the crystal structure but can also broaden the band gap and enlarge the laser damage threshold (LDT) .…”
Section: Figurementioning
confidence: 99%
“…-based iodatefluorides, such as 3.97 eV for Bi(IO 3 )F 2 [47], 2.39 eV for CsVO 2 F(IO 3 ) [6] and 2.6 eV for Ce(IO 3 ) 2 F 2 •H 2 O [48]. Hence, it is believed that both fluoride anions and blueshift cations such as Ga 3+ cation can widen the band gaps of metal iodates.…”
Section: +mentioning
confidence: 99%
“…To the best of our knowledge, the study of metal polyiodates only involves the alkali metal or Ag + and Ba 2+ iodate systems. Many rare‐earth iodates also possess excellent SHG properties, for example, La(IO 3 ) 3 has a large SHG signal of roughly 400× SiO 2 . Accordingly, the combination of a trivalent metal cation such as RE 3+ and a polyiodate anion is expected to afford new SHG materials.…”
Section: Methodsmentioning
confidence: 99%